2002
DOI: 10.1097/00008571-200208000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The efficacy of the immunosuppressants azathioprine and 6-mercaptopurine has been well established in the therapy of inflammatory bowel diseases (IBD). However, its use has been complicated by a high incidence of serious adverse drug reactions such as hematotoxicity, hepatotoxicity, pancreatitis and gastrointestinal disturbances. Whereas azathioprine-related pancytopenia has been clearly linked to thiopurine S-methyltransferase (TPMT) polymorphism limited data are available to explain gastrointestinal side eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(51 citation statements)
references
References 41 publications
2
47
1
1
Order By: Relevance
“…The levels did show an overall correlation with drug dose; however, there was a wide variability in individual cases. A high 6‐MMP level predisposes to the risk of hepatotoxicity 8. None of our patients had 6‐MMP level >5700 pmol/8 × 10 8 RBCs or hepatotoxicity.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The levels did show an overall correlation with drug dose; however, there was a wide variability in individual cases. A high 6‐MMP level predisposes to the risk of hepatotoxicity 8. None of our patients had 6‐MMP level >5700 pmol/8 × 10 8 RBCs or hepatotoxicity.…”
Section: Discussionmentioning
confidence: 52%
“…The drug is metabolized by multistep, multienzymatic pathways leading to wide interindividual variability. It is difficult to clinically optimize thiopurine therapy in IBD patients and 28% of patients have hepatotoxic and myelotoxic adverse reactions, and 9% of patients are resistant to therapy 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that in Japanese patients complete blood count should be monitored monthly during the first year of therapy. Among Caucasian patients with inflammatory bowel disease adverse drug reactions to AZA or 6-MP were reported to occur in 15–20% and myelosuppression in 5–10% [9,10,11,12,13]. The reason for the difference in the incident of myelosuppression between this study on Japanese children and on the reported incidence in Caucasians might be derived from the different genetic background effects on thiopurine drug metabolism.…”
Section: Discussionmentioning
confidence: 60%
“…67 The occurrence of leukopenia by TPMT activity was taken from two studies of patients with inflammatory bowel disease who were treated with azathioprine. 102,103 A weighted average was calculated, showing that 5% of patients with normal TPMT activity, 21.4% with intermediate activity and 100% with no activity developed leukopenia following full-dose azathioprine. It was assumed from studies in alveolar haemorrhage and atopic dermatitis that a reduced dose would half the risk to 10%.…”
Section: Modelling Approachmentioning
confidence: 99%